1976
DOI: 10.1007/bf01577249
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of ego identity development at a liberal arts college

Abstract: Ego identity development in the areas of occupational choice, religion, and political ideology was studied using Marcia's categorization system. The results indicated a significant increase in the frequency of the identity achiever status for occupational choice and corresponding decreases in the frequency of the moratorium and identity diffusion statuses. A significant decrease in the frequency of foreclosures on religion was also found. In those instances where students underwent an identity crisis, the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 6 publications
1
35
0
1
Order By: Relevance
“…A limited number of longitudinal studies (Adams & Fitch, 1982;Dellas & Jernigan, 1987;Kroger, 1988;Meeus, Iedema, Helsen, & Vollebergh, 1999;Waterman, Geary, & Waterman, 1974;Waterman & Goldman, 1976;Waterman & Waterman, 1971) have tested whether transitions out of some statuses (e.g., diffusion) are more prevalent than transitions into those statuses. The available findings suggest that in cases where adolescents do change statuses, more adolescents move out of diffusion than into it (in about 30% of the studies), more into than out of achievement (in about 50% of the studies), more out of than into foreclosure (in about 22% of the studies), and more out of than into moratorium (in about 29% of the studies).…”
Section: Identity Statuses: Individual Differences or Development?mentioning
confidence: 99%
“…A limited number of longitudinal studies (Adams & Fitch, 1982;Dellas & Jernigan, 1987;Kroger, 1988;Meeus, Iedema, Helsen, & Vollebergh, 1999;Waterman, Geary, & Waterman, 1974;Waterman & Goldman, 1976;Waterman & Waterman, 1971) have tested whether transitions out of some statuses (e.g., diffusion) are more prevalent than transitions into those statuses. The available findings suggest that in cases where adolescents do change statuses, more adolescents move out of diffusion than into it (in about 30% of the studies), more into than out of achievement (in about 50% of the studies), more out of than into foreclosure (in about 22% of the studies), and more out of than into moratorium (in about 29% of the studies).…”
Section: Identity Statuses: Individual Differences or Development?mentioning
confidence: 99%
“…These findings are consistent with the results presented by (Berzonsky, 2000;Farsinejad, 2004). Adams and Fitch (1982) Waterman et al (1974 as well as Waterman and Goldman (1976) showed over time sense of personal identity increases (Waterman, 1974;Adams, 1982;Waterman, 1999). Akhavan (2004) also found that there was no relationship between the individual characteristics (age, sex, and years of education), physical structure of the family (number of children, sex of the children, and order of birth and social position of the parents) and the formation of adolescent identity.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous study found that the pattern of identity development for the liberal arts and engineering students is generally similar (Waterman and Goldman 1976), future studies should include samples with a more balanced composition.…”
Section: Implications Limitations and Conclusionmentioning
confidence: 91%